Hubungan Fasilitas Belajar Di Rumah dengan Hasil Belajar Matematika Siswa Kelas IV SDN 113 Inpres Tiromanda - Eky Setiawan Salo (LPPM UKI Toraja, 2022)
The purpose of this study was to determine whether there is a relationship between learning facilities at home and the mathematics learning outcomes of IV grade students at SDN 113 Inpres Tiromanda. This study uses a quantitative approach with the type of correlation research and is analyzed using the help of Statistical Product and Service Solutions (SPSS). This research because all members of the population are sampled, namely 33 people. Data collection technique in this study are documentation and questionnaires. Documentation technique is used to obtain data on the value of students’ mathematics learning outcomes and documentation when conducting research. Questionnaire technique is used to obtain data about learning facilities at home for IV grade students. Based on the results of data analysis with the product moment correlation test, it can be concluded that there is a relationship between learning facilities at home and the mathematics learning outcomes of IV grade students at SDN 113 Inpres Tiromanda. This is evidenced by the result of research and analysis of the data obtained, that thitimt 0,631 >tabd 0,344. Therefore, the hypothesis Ha in the study is accepted and the hypothesis Ho is rejected.